Lost in Translation: Exploring Major Challenges Encountered by Tunisian EFL Learners Translating between English and Arabic - Mohamed Hajjej (Yayasan Visi Intan Permata, 2025)
It is widely believed that translation is not only a process of transferring a source text into a target text, but also a complicated challenge of conveying to the readers of the target text the meaning of a source text, in which a translator should always take into account and pay attention to the message equivalence of both texts. Such complexity originates from the fact that a translator must, on the one hand, fully understand the content of the source material in order to provide accurate and acceptable translations and, on the other hand, pay full attention to all parts of language, such as meaning, syntax, style, and sounds, which are equally important in the translation process, as failure to observe any of them will result in meaning distortion, as strictly noted by Ghazala (2008). Working on a group of students’ responses to three translation tasks and on classroom observation of these students while engaged in translation practices for a whole term, the following research paper using both qualitative and quantitative analyses sets out to explore major challenges encountered by Tunisian EFL learners when engaged in the process of translating between English and Arabic, focusing on the main sources of those challenges, and attempting to offer some possible solutions to alleviate the impact of such challenges on learners’ performance related to translation practices.